Optimalisasi Digital Marketing dan E-Commerce Berbasis Notifikasi untuk Meningkatkan Penjualan UMKM Kampoenk Snack Probolinggo - Moh. Ainol Yaqin; Matlubul Khairi; Rizki Febri Eka Pradani (Universitas Nurul Jadid, 2025)
This community service program (PkM) strengthened the competitiveness of Kampoenk Snack MSME (Probolinggo) by raising partner empowerment in management (income generating) and marketing (revenue generating). Baseline conditions showed manual operations: inconsistent transaction and cashflow records, low traceability, and limited digital penetration (online sales <20%, rating 4.3 with <30 reviews). The program applied Participatory Action Research (PAR) in five stages: socialization, training, technology deployment, mentoring–evaluation, and sustainability. Interventions were grouped into (1) management–finance digitalization via a simple accounting/recording app, standardized workflows, and monthly profit–loss reporting; and (2) digital marketing automation through marketplace restructuring, improved content, and notification-based e-commerce (WhatsApp Fonnte, Telegram Bot, email marketing, auto-responder), with WhatsApp direct messages as the primary conversion channel. Performance measures included a management regularity checklist, marketplace dashboards for rating and reviews, notification logs, and content insights. Measurement windows were two weeks for content reach and two months for online revenue. Data were triangulated by cross-checking app records, marketplace recaps, transaction evidence, interviews, and observations. Results show management regularity improved to 85%, promotions reached >300 customers, 15 photos and 5 videos reached 5,000 accounts in two weeks, online revenue rose 30% (IDR 2.75 million to IDR 3.5–4 million/month), and marketplace reputation increased (reviews 28→53; rating 4.3→4.7).